2021
DOI: 10.1021/acsami.1c14563
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lasting Luminol Chemiluminescence Emission with 1,10-Phenanthroline-2,9-dicarboxylic Acid Copper(II) Complex on Paper

Abstract: As most of the known systems are flashtype, long-lasting chemiluminescence (CL) emissions are extremely needed for the application of cold light sources, accurate CL quantitative analysis, and biological mapping. In this work, the flashtype system of luminol was altered to a long lasting CL system just because of the paper substrate. The Cu­(II)-based organic complex was loaded on the paper surface, which can trigger luminol-H2O2 to produce a long lasting CL emission for over 30 min. By using 1,10-phenanthroli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Chemiluminescence (CL) is a phenomenon of radiation produced by a chemical reaction without external excitation, which has been widely used for bioassays, imaging, and illumination applications. , The commercial CL bioassay is usually divided into glow and flash fashions. Flash fashion CL occurs quickly, , while glow fashion CL displays a slow kinetic emission curve. , CL for both basic research and commercial bioassay is mainly conducted in the eye-visible region with a molecular luminophore, such as luminol, peroxy oxalate, dioxetane, lucigenin, KMnO 4 , and lophenol . The waveband of molecular CL is limited to 780 nm, , and near infrared (NIR) emission is strongly anticipated for CL evolution.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Chemiluminescence (CL) is a phenomenon of radiation produced by a chemical reaction without external excitation, which has been widely used for bioassays, imaging, and illumination applications. , The commercial CL bioassay is usually divided into glow and flash fashions. Flash fashion CL occurs quickly, , while glow fashion CL displays a slow kinetic emission curve. , CL for both basic research and commercial bioassay is mainly conducted in the eye-visible region with a molecular luminophore, such as luminol, peroxy oxalate, dioxetane, lucigenin, KMnO 4 , and lophenol . The waveband of molecular CL is limited to 780 nm, , and near infrared (NIR) emission is strongly anticipated for CL evolution.…”
mentioning
confidence: 99%
“…Flash fashion CL occurs quickly, 3,4 while glow fashion CL displays a slow kinetic emission curve. 5,6 CL for both basic research and commercial bioassay is mainly conducted in the eye-visible region with a molecular luminophore, such as luminol, 7 peroxy oxalate, 8 dioxetane, 9 lucigenin, 10 KMnO 4 , 11 and lophenol. 10 The waveband of molecular CL is limited to 780 nm, 9,12−14 and near infrared (NIR) emission is strongly anticipated for CL evolution.…”
mentioning
confidence: 99%
“…According to the work of Zang et al, O 2 •– and H 2 O 2 could generate OH • , which explained the source of OH • in this CL system. In the work of Lv et al, O 2 •– could generate H 2 O 2 and 1 O 2 , which supported the existence of 1 O 2 . The mechanism of the Zn-Py-TPE-TCPO system can be seen in Scheme .…”
Section: Resultsmentioning
confidence: 81%
“…The comparison results in Figure S7 indicated that the above mechanism was suitable for the Zn-Py-TPE-TCPO system. According to the work of Zang et 43 which supported the existence of 1 O 2 . The mechanism of the Zn-Py-TPE-TCPO system can be seen in Scheme 2.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Paper 32 as an appropriate substrate makes great contributions to MOFs' immobilization and provides a sufficient reacting carrier. 33 UiO-66 was synthesized by an in situ method on the paper surface. After acetone was adsorbed by the UiO-66@paper, CL reagents in the liquid phase were added to permeate the whole paper.…”
Section: Introductionmentioning
confidence: 99%